Nitrogen enrichment alters the resistance of a noninvasive alien plant species to Alternanthera philoxeroides invasion - Wu, Hao; Dong, Sijin; Wang, Li; Zhu, Yuanyuan; Jia, Shaoqi; Rao, Benqiang (Frontiers in Ecology and Evolution, 2023)
Soil nitrogen can significantly affect the morphology, biomass, nutrient allocation, and photosynthesis of alien vs. native plants, thereby changing their coexistence patterns; however, the effect of soil nitrogen on the interspecific relationship between alien plants is currently unclear. We conducted a nitrogen addition experiment in a greenhouse to explore the effect of soil nitrogen on the interspecific relationship between invasive alien weed Alternanthera philoxeroides and the noninvasive alien horticultural plant Oxalis articulata. We set three experimental factors—nitrogen treatment, planting type, and species and measured the morphology, biomass, carbon (C) and nitrogen (N) content, physiological traits, and photosynthetic fluorescence of the studied plant species. We then used multi-way ANOVA and multiple comparisons to examine the differences in the above indicators among treatment combinations. We found that, in mixed cultures, nitrogen addition significantly increased the root area of O. articulata by 128.489% but decreased the root length by 56.974% compared with the control, while it significantly increased the root length of A. philoxeroides by 130.026%. Nitrogen addition did not affect the biomass accumulation of these two plant species; however, the biomass and root/shoot ratio of O. articulata were significant higher than those of A. philoxeroides. Nitrogen addition significantly increased the N content of A. philoxeroides by 278.767% and decreased the C:N ratio by 66.110% in mixed cultures. Nitrogen addition caused a significant trade-off between flavonoid and anthocyanin in O. articulata, and decreased the initial fluorescence (F0) and maximal fluorescence (Fm) of A. philoxeroides by 18.649 and 23.507%, respectively, in mixed cultures. These results indicate that nitrogen addition increased the N absorption and assimilation ability of A. philoxeroides in deep soil; furthermore, it significantly enhanced the advantages for O. articulata in terms of morphology, physiological plasticity, and photosynthetic efficiency. In addition, O. articulata had better individual and underground competitive advantages. Under intensified nitrogen deposition, the biotic replacement effect of O. articulata on A. philoxeroides in natural ecosystems could be further enhanced.